Analisis Pengaruh Literasi Keuangan, Inklusi Keuangan, Dan Tingkat Pendidikan Terhadap Perilaku Keuangan Pelaku Umkm Kedai/Warung Makanan Di Desa Bahagia Kabupaten Bekasi - Puput Andriyani; Ari Sulistyowati (Aliansi : Jurnal Manajemen dan Bisnis, 2021)
This study aims to determine the effect of financial literacy on financial behavior, the effect of financial inclusion on financial behavior, and the effect of education level on financial behavior. The method in data processing used in this research is to use PLS (Partial Least Square) with the object of research being SMEs in the food stalls/shops in the Bahagia Village, Bekasi Regency. The sampling technique used was purposive probability with the form of non-probability sampling. The data collection technique used a questionnaire as many as 106 SMEs in the food stalls/shops in the Bahagia Village, Bekasi Regency. The results of this study indicate that there is a significant influence of financial literacy on the financial behavior of SMEs in food stalls/food stalls in Bahagia Village with t statistics 2.618 greater than t table 1.659, and a significant value of financial inclusion on financial behavior with t statistics 2.462 greater than t table 1.659, as well as the significant value of education level on the financial behavior of SMEs in food stalls/shops in Bahagia Village with a t statistics of 2.689 which is greater than a t table of 1.659.